EVALUASI INFORMASI GEOSPASIAL DALAM TAHAP PENETAPAN BATAS DAERAH PADA ERA OTONOMI DAERAH DI INDONESIA - , WULANSARI E ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One phenomenon that appears accompanying the implementation of regional autonomy in Indonesia is a regional division. In a period of 10 years (1999 to 2009) was formed 194 new autonomous regions. Regional expansion means adding segment boundary. The formation of autonomous regions is done through the political process by the Parliament and the Government ranging from local to central level and the result is the Law on the Formation Regions in which regulates the establishment and the scope and boundaries of the area are formed. In theory, the process of delimitation of the area is part of the boundary phases in the making. In every stage of making the necessary boundary geospatial information (GI) are technically qualified and appropriate mapping survey boundary rule making. The research question asked whether the IG used in the delimitation area which has been done in the era of regional autonomy is in compliance with such requirements? It is necessary for evaluation. GI evaluation stage area delimitation performed on stage inputs, processes and outputs. GI evaluated data was in the process of formation of new autonomous regions. At the input stage-setting, evaluation measures was the availability and quality of geospatial information refer to PP/8/2003 on the map, and compare the accuracy of the Terms of Reference (TOR) and Specifications Map RBI (SPR) with Indonesian National Standard (SNI) of the RBI Map . GI evaluation benchmark-setting process are the rules according to the theory of boundary delimitation making Jones. IG evaluation measures on the outer map requirements delimitation was the result of delimitation according to Adler. The results showed that in the period 1999 to 2007 which refers to the regulation of PP/129/2000 on the Establishment Requirements, Elimination and Merging Autonomous Region, maps attachment Establishment Act is not entirely autonomous region using geospatial information is correct according to the rules of geodesy. This resulted in the attachment of Law Formation Regions in the period 1999 to 2007, 57% do not have a scale, the entire map is not included geodetic datum and coordinate system are obvious. In the period after the PP/129/2000 was replaced by PP/78/2007, Indonesia RBI maps should be used as the basis for creating the map attachment Regional Establishment Act. With the use of RBI maps of Indonesia, the geodetic datum and coordinate system are listed on the map attachment statute, so the map attachment becomes clearer and easier for implementation in the field boundary assertion.